2022
DOI: 10.48153/jrrs/2010/yawt6262
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Lead rubber aprons in Radiodiagnostic centres in South-South Nigeria

Abstract: Background of Study: Radiation protection is of core importance in radiodiagnostic centres, to keep both patients care givers and staff of the centres from stochastic and non- stochastic effects of radiation. The effectiveness and protectiveness of aprons are of valuable importance, it is therefore necessary to assess these aprons to ensure efficacy. Such quality checks have not been reported in the South – South region of Nigeria. Aim: To assess in terms of their quality and therefore protective features, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
2
4
1
Order By: Relevance
“…The study also revealed that the most common type of defect is splits (separation) which account for 42.0% which differs from the results obtained in other studies where cracks were the major defects, accounting for 44% [16], 60% [15], 56.25% [13], and 70% [17]. The protective apparel's integrity deteriorates as it ages; however, the level of damage observed on the aprons was not necessarily dependent on the age of the apron but may also be attributed to poor handling by the users, as folding and dropping of aprons were observed in some of the hospitals, which could be one of the major causes of rips, cracks, and holes in the protective apparel.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The study also revealed that the most common type of defect is splits (separation) which account for 42.0% which differs from the results obtained in other studies where cracks were the major defects, accounting for 44% [16], 60% [15], 56.25% [13], and 70% [17]. The protective apparel's integrity deteriorates as it ages; however, the level of damage observed on the aprons was not necessarily dependent on the age of the apron but may also be attributed to poor handling by the users, as folding and dropping of aprons were observed in some of the hospitals, which could be one of the major causes of rips, cracks, and holes in the protective apparel.…”
Section: Discussioncontrasting
confidence: 99%
“…About 11 (92%) of the defects observed exceeded the maximum area 15 mm 2 and 10 cm 2 for rejection and replacement as recommended by Lambert & McKeon [12] and Duran & Phillips [20], as well as Sam & Pillay [4], which states that the maximum tolerable length of a defect on a whole-body garment with the lead equivalent of 0.25 mm, 0.35 mm, and 0.5 mm should not exceed 5.4 cm, 5.6 cm, and 5.9 cm respectively. Furthermore, about 83.0% of defects were noticed in protective apparel with no manufacturer's name, which is in tandem with what was recorded by Ukpong [16], who reported 81% of defects found on the apron with no manufacturer's name.…”
Section: Discussionsupporting
confidence: 77%
“…In studies by Oyar O et al in Turkey [6] and Ryu Sung J et al in South Korea [8], leaded aprons were used for less than 6 years. On the other hand, Ukpong E. V. et al [5] found in their series aprons that had been in use for more than 40 years. This shows that recommendations NF C 74-100 and C EI61-331-3 are not respected in Africa.…”
Section: Discussionmentioning
confidence: 98%
“…This sample is representative in view of the samples from similar studies. The study by Ukpong et al [5] involved 22 leaded aprons. The study by Ryu Sung et al [8] involved 71 leaded aprons and 27 thyroid protectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation